2018
DOI: 10.1589/jpts.30.595
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking and aerobic exercise on male college students’ metabolic syndrome risk factors

Abstract: [Purpose] The aim was to investigate the effects of university students’ smoking and aerobic exercise on metabolic syndrome risk factors. [Subjects and Methods] Twenty-three male students were randomly assigned to the following groups: exercise smoker (n=6), non-exercise smoker (n=6), exercise non-smoker (n=6), and non-exercise non-smoker (n=5). A basketball exercise program was conducted three times per week (70 minutes per session) for 8 weeks with exercise intensity set at 50–80% of heart rate reserve. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“…many studies have found a positive association between conventional cigarette smoking and the metabolic syndrome [7][8][9][10][11] , few have examined the effects of e-cigarettes, on MetS and/or its risk factors.…”
mentioning
confidence: 99%
“…many studies have found a positive association between conventional cigarette smoking and the metabolic syndrome [7][8][9][10][11] , few have examined the effects of e-cigarettes, on MetS and/or its risk factors.…”
mentioning
confidence: 99%
“…Otra variable importante es la actividad física, donde el 58,7 % lleva una vida sedentaria que está relacionada con las cargas académicas grandes que conlleva el pregrado de Medicina, evidenciado por el tiempo que permanecen sentados, con un número de 110 personas que permanecen entre 6 y 10 horas sentadas al día (18). Los factores de riesgo cardiovascular están relacionados con aumento de peso, sedentarismo y agentes externos que aportan al deterioro futuro (19,20); en este caso, observamos que el 4,29 % son catalogados como fumadores leves.…”
Section: Discussionunclassified
“…The energy and nutritional contents of the provided Japanese-style healthy lunch menu were based on the Guidelines for the Diagnosis and Prevention of Atherosclerotic Cardiovascular Diseases (Japan Atherosclerosis Society, 2007) [9]. The criteria for vegetable intake matched those recommended by Healthy Japan 21.…”
Section: Concept Of a Japanese-style Healthy Lunch Menumentioning
confidence: 99%
“…Exercise and diet are important factors for the prevention and improvement of MS [7][8][9]. From interventional study reports, Mediterranean diet is effective for the prevention and improvement of MS and abdominal obesity [10,11].…”
Section: Introductionmentioning
confidence: 99%